142+x=64+3x

Simple and best practice solution for 142+x=64+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 142+x=64+3x equation:


Simplifying
142 + x = 64 + 3x

Solving
142 + x = 64 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
142 + x + -3x = 64 + 3x + -3x

Combine like terms: x + -3x = -2x
142 + -2x = 64 + 3x + -3x

Combine like terms: 3x + -3x = 0
142 + -2x = 64 + 0
142 + -2x = 64

Add '-142' to each side of the equation.
142 + -142 + -2x = 64 + -142

Combine like terms: 142 + -142 = 0
0 + -2x = 64 + -142
-2x = 64 + -142

Combine like terms: 64 + -142 = -78
-2x = -78

Divide each side by '-2'.
x = 39

Simplifying
x = 39

See similar equations:

| 5(r-10)=2(r-4)-6 | | 5+35=125 | | 12v-8(8v)= | | 3b+11=50 | | 5x+4y=1.5 | | 2x+(45-6x)=17 | | x=43x*2 | | 1.2c+5=1.4 | | 120X=4000-160X | | -7+5y=-37 | | x^4+81y^4=165-xy | | 2u+8=2 | | 4100=4000c-500 | | 16-6(-3x+4)=-2 | | 2x-9=6x+4 | | c/5-4=3 | | 38+x=2x+6x-2 | | 8*w=52 | | 16-6(-3x+4)=2 | | 31-4x=5x+19 | | 22=8x+1-5X | | x^2+17x+31=4x-5 | | 24+-2a+3=7a | | 5(3-x)=-(1+x) | | x^2+x-18=2 | | -24=-4(k+3) | | 7h-7=17+4h | | y=x^2-7x+6 | | -2x+4=3(x-7) | | 21+9y-10=-277 | | 7x+9=8x+4 | | -7(x+9)=8x+42 |

Equations solver categories